Estudio Etnográfico del Patrimonio Cultural de la parroquia San Pablo, cantón San Miguel, provincia Bolívar, 2017 - Carmona Berrezueta, Gladis Samantha (2018)
The ethnographic study in the San Pablo parish of the Bolívar province exposes a description and interpretation of the people, the local culture, identifying the practices of their way of life that allows to have a global vision of the social environment. This research allows the local population to have a total independence of education of what they have learned or will learn in relation to their cultural manifestations and that allows them to have their own criteria, their own values, allowing to maintain conditions of respect with other social groups. To achieve the results the following methodology was proposed in relation to each objective in this way for the fulfillment of the first objective the survey of socio-cultural diagnosis of the city of San Pablo, the review of secondary bibliographical sources of the fields was considered: spatial physics , economic productive, sociocultural and political administrative; for the fulfillment of the second objective that was to carry out the inventory of existing cultural attractions, the methodology of the National Institute of Cultural Heritage of Ecuador was applied; Finally, for the fulfillment of the third objective, which was the realization of a rescue proposal and dissemination of the ethnographic elements, strategies were defined to improve the ethnographic conditions, making the profiles of programs and projects. In this way it was possible to know the most important characteristics of the parish in the geographical, productive and sociocultural context that allows to have a description of the activities, scene and subjects of study; the parish of São Paulo in Athens has 14 relevant cultural assets, 9 of which are traditions, 4 are public spaces and 1 are knowledge. In order to generate a contribution of the study, a proposal was established to rescue the most representative ethnographic elements of the San Pablo parish, consider aspects that provide opportunities that will allow establishing strategies to revitalize the cultural and find mechanisms for its dissemination.